Sural nerve and short saphenous vein entrapment-a case report - Satheesha, B Nayak (Indian Journal of Plastic Surgery, 2005)
Although the sural nerve is the most extensively studied nerve in man, there is a dearth of data regarding the normal variations in the size and distribution of axons in normal subjects. Since the sural nerve is the most frequently used sensory nerve in nerve transplantation, knowledge of variations in its course and distribution plays an important role in the surgical procedures. Here, an entrapment of the sural nerve in the gastrocnemius is reported. The short saphenous vein also passed through the gastrocnemius muscle along with the sural nerve.
Keywords: Sural nerve; Entrapment; Short saphenous vein